University of Florida/IFAS Ornamental Plant Improvement Program: Three Caladium, Two Gerbera, and Thirteen Lisianthus Cultivars Released in 2005: ENH1051/EP328, 4/2007 - Deng, Zhanao; Harbaugh, Brent K. (EDIS, 2007)
ENH-1051, a 5-page fact sheet by Zhanao Deng and Brent K. Harbaugh, describes the characteristics of new ornamental plant cultivars released in 2005. Includes references. Published by the UF Department of Environmental Horticulture, April 2007.